Barriers to cervical cancer screening and acceptability of HPV self-testing: a cross-sectional comparison between ethnic groups in Southern Thailand. Issue 11 (3rd November 2019) - Gottschlich, Anna; Nuntadusit, Thanatta; Zarins, Katie R; Hada, Manila; Chooson, Nareerat; Bilheem, Surichai; Navakanitworakul, Raphatphorn; Nittayaboon, Kesara; Virani, Shama; Rozek, Laura; Sriplung, Hutcha; Meza, Rafael
Abstract : Background: Cervical cancer rates are higher in low-resourced countries than high, partly due to lower rates of screening. Incidence in Thailand is nearly three times higher than in the USA (16.2 vs 6.5 age-standardised incidence), even with Thailand's universal health coverage, which includes screening, suggesting that alternative methods are needed to reduce the burden. We investigated barriers to screening, as well as acceptability of self-collection human papillomavirus (HPV) testing as a primary form of cervical cancer screening among Buddhist and Muslim communities in Southern Thailand. Methods: 267 women from the Buddhist district of Ranot and Muslim district of Na Thawi, Songkhla were recruited to complete a survey assessing knowledge and risk factors of HPV and cervical cancer. Participants were offered an HPV self-collection test with a follow-up survey assessing acceptability. Samples were processed at Prince of Songkhla University and results were returned to participants. Results: 267 women participated in the study (132 Buddhist, 135 Muslim), 264 (99%) self-collecting. 98% reported comfort and ease, and 70% preferred it to doctor-facilitated cytology. The main predictor of prior screening was religion (92% Buddhist vs 73% Muslim reporting prior Pap). After adjustment with multivariate logistic models, Muslim women had an OR of prior Pap of 0.30 compared with Buddhist (95% CI: 0.12 to 0.66). Conclusions: Self-collection HPV testing was highly acceptable across religious groups, suggesting that it could be beneficial for cervical cancer reduction in this region. Focus should be put into educating women from all backgrounds about the importance of screening to further improve screening rates among Thai women.